Cocaine Dysregulates Dynorphin Modulation of Inhibitory Neurotransmission in the Ventral Pallidum in a Cell-Type-Specific Manner - Inbar, Kineret (J Neurosci, 2020)
Cocaine-driven changes in the modulation of neurotransmission by neuromodulators are poorly understood. The ventral pallidum (VP) is a key structure in the reward system, in which GABA neurotransmission is regulated by opioid neuropeptides, including dynorphin. However, it is not known whether dynorphin acts differently on different cell types in the VP and whether its effects are altered by withdrawal from cocaine. Here, we trained wild-type, D1-Cre, A2A-Cre, or vGluT2-Cre:Ai9 male and female mice in a cocaine conditioned place preference protocol followed by 2 weeks of abstinence, and then recorded GABAergic synaptic input evoked either electrically or optogenetically onto identified VP neurons before and after applying dynorphin. We found that after cocaine CPP and abstinence dynorphin attenuated inhibitory input to VP(GABA) neurons through a postsynaptic mechanism. This effect was absent in saline mice. Furthermore, this effect was seen specifically on the inputs from nucleus accumbens medium spiny neurons expressing either the D1 or the D2 dopamine receptor. Unlike its effect on VP(GABA) neurons, dynorphin surprisingly potentiated the inhibitory input on VP(vGluT2) neurons, but this effect was abolished after cocaine CPP and abstinence. Thus, dynorphin has contrasting influences on GABA input to VP(GABA) and VP(vGluT2) neurons and these influences are affected differentially by cocaine CPP and abstinence. Collectively, our data suggest a role for dynorphin in withdrawal through its actions in the VP. As VP(GABA) and VP(vGluT2) neurons have contrasting effects on drug-seeking behavior, our data may indicate a complex role for dynorphin in withdrawal from cocaine. SIGNIFICANCE STATEMENT The ventral pallidum consists mainly of GABAergic reward-promoting neurons, but it also encloses a subgroup of aversion-promoting glutamatergic neurons. Dynorphin, an opioid neuropeptide abundant in the ventral pallidum, shows differential modulation of GABA input to GABAergic and glutamatergic pallidal neurons and may therefore affect both the rewarding and aversive aspects of withdrawal. Indeed, abstinence after repeated exposure to cocaine alters dynorphin actions in a cell-type-specific manner; after abstinence dynorphin suppresses the inhibitory drive on the “rewarding” GABAergic neurons but ceases to modulate the inhibitory drive on the “aversive” glutamatergic neurons. This reflects a complex role for dynorphin in cocaine reward and abstinence.